Landslide disaster mitigation training using the vegetative method in the Kasepuhan Traditional Village, Sukabumi Regency - Ruwaida Zayadi; Sih Andajani; Etty Indrawati; Ilman Himawan Kusumah; Nadia Karya Alam (Universitas Muhammadiyah Magelang, 2022)
The slopes have the capacity to collapse, which worries the residents of the Traditional Village in Sinar Resmi Village about the risk of it happening again after the landslide disaster at the beginning of 2019. This community service strives to educate about the mitigation of the risk of landslides. The pre-disaster preparations and training to create mitigation pilots with a vegetative approach that makes use of native plant species that are already familiar to the community make up the method adopted. This approach is based on research findings that investigate the function of plant roots in fortifying soil on slopes, which can improve stability. As a result of this program, the villagers are aware of the precautions to take before a disaster to prevent landslides, and they have learned from the pilot project how important vegetation roots are for slope stability based on their root systems. It is intended that, in the future, the Kasepuhan Traditional Village community would be able to conserve land on its own using vegetative approaches.